Thermally assisted optically stimulated luminescence protocol of mobile phone substrate glasses for accident dosimetry. (August 2021) - Kim, Hyoungtaek; Discher, Michael; Kim, Min Chae; Woda, Clemens; Lee, Jungil
Abstract: A thermally assisted optically stimulated luminescence protocol for the use of display glass samples from mobile phones as a fortuitous dosimeter was developed. Glass samples from 16 different mobile phones from the Samsung Galaxy series were used. The protocol consists of a prebleach with LEDs of 470 nm for 500 s and an OSL reading for 500 s at an elevated temperature. The decay curves were measured at different temperatures from 100 to 400 °C in an interval of 50 °C. A significant baseline increase in the decay curves was observed above 350 °C. For the TA-OSL below 300 °C, the dose response from 10 mGy to 10 Gy was linear and the signals were reproducible within 5% for six repeated readings. Compared with the residual thermoluminescence after an isothermal reading, the TA-OSL protocol showed lower zero doses at the given temperature. By increasing the temperature of the TA-OSL protocol from 100 to 300 °C, the minimum detectable dose increased from 17 to 70 mGy, but the fading rate reduced from 64% to 36% after 41 days from irradiation. In the optical stability test, strong reductions in TA-OSL signals were observed after exposures up to 1000 s with several light sources, and it was found that violet LEDs are more effective than blue LEDs for bleaching. As a result, the TA-OSL protocols investigated showed some improvements in terms of the lower minimum detectable doses and reduced fading rates compared with the prebleached thermoluminescence protocol. Highlights: TA-OSL protocol of display glasses was developed for dose reconstructions in a radiological emergency. TA-OSL protocol exhibits a maximum detection limit of 70 mGy. TA-OSL at 300 °C showed a signal loss of 36% after 41 days.